Pomegranate Peel Extract as an Inhibitor of SARS-CoV-2 Spike Binding to Human ACE2 Receptor (in vitro): A Promising Source of Novel Antiviral Drugs - Tito, Annalisa; Colantuono, Antonio; Pirone, Luciano; Pedone, Emilia; Intartaglia, Daniela; Giamundo, Giuliana; Conte, Ivan; Vitaglione, Paola; Apone, Fabio (Frontiers in Chemistry, 2021)
Plant extracts are rich in bioactive compounds, such as polyphenols, sesquiterpenes and triterpenes, with potential antiviral activities. As the dramatic outbreak of the pandemic COVID-19, caused by the SARS-CoV-2 virus, thousands of scientists are working tirelessly trying to understand the biology of this new virus and the disease pathophysiology, with the main goal to discover effective preventive treatments and therapeutic agents. Plant-derived secondary metabolites may play key roles in preventing and counteracting the rapid spread of SARS-CoV-2 infections by inhibiting the activity of several viral proteins, in particular those involved in the virus entry into the host cells and its replication. By using in vitro approaches, we investigated on the role of a pomegranate peel extract in attenuating the interaction between the SARS-CoV-2 Spike glycoprotein and the human Angiotensin-Converting Enzyme 2 (ACE2) receptor, and on the activity of the virus 3CL protease. Although further studies will be determinant to assess the efficacy of this extract in vivo, our results open up new promising opportunities to employ natural extracts for the development of effective and innovative therapies in the fight against SARS-CoV-2.